Students' Perception Towards the Implementation of Project Based-Learning in Geographic Information System Course - Halim, Rd.; Syukri, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2024)
Project Based Learning (PJBL) is a learning model that can organize projects in learning. PJBL can provide opportunities for a student-centered learning system. This learning model is believed to be able to provide solutions to the problems of the education process in Indonesia which is still not optimal. Geographic Information Systems course is a compulsory course in epidemiology specialization. The main objective of the study was to determine student perceptions of the application of the PjBL model in the Geographic Information Systems course. This study used a cross-sectional study design with a sample size of 37 students. Data collection was carried out using a structured questionnaire that had been tested for validity and reliability. Data processing and analysis using IBM SPSS 25.0 software. The results showed that students' perceptions of the implementation of GIS course PJBL predominantly agreed followed by strongly agreed with the implementation of PJBL. This study concludes that student perceptions of the implementation of PPA in Geographic Information Systems courses are very good.